Pelayanan Publik Dan Kinerja Pegawai Terhadap Kesadaran Adminduk Melalui Kalimasada Di Kelurahan Gebang Putih Surabaya - Nani Septiana; Kuncoro Budi Riyanto; Rismawati, Dina (Universitas Muhammadiyah Metro, 2024)
This study aimed to find out the role of public services and employee performances inincreasing public awareness of population administration through the PopulationAdministration Aware Community Environment Program (KALIMASADA) in Gebang PutihVillage, Surabaya City. The public services and employee performances which assisted by theKALIMASADA program are later on expected to increase awareness for the public who donot yet know about the importance of population administration. This research was aqualitative research with a descriptive approach applied data collection techniques throughinterviews, observation and documentation. The data analysis techniques used reduction,data presentation and conclusion. The results of the study showed that the role of publicservants and employee performance in increasing public awareness of populationadministration (adminduk) has been well implemented. However, there are several thingsthat must be improved, such as supporting infrastructure so that services run optimally, thenthe efforts to improve the quality of human resources (HR) in the Gebang Putih Village areexpected to be involved in training to expedite the service process. With the KALIMASADAprogram, population document management activities in the Gebang Putih sub-district haveincreased in order to be more responsive in giving service and increasing the public interestin managing administrative documents.